Model Creation of Musical String Instrument Based on Ethnic Diversity in North Sumatera - Suroso, Panji; Hasbulah, Mulkis; Wiastuti, Uyuni; Hirza, Herna; Silionga, Pita HD; Amal, Bakhrul Khair (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This research is based on the curiosity about the phenomenon of the diversity of concepts and organizational structures of traditional stringed instruments in North Sumatra to be developed in finding new, more innovative concepts in creating North Sumatra local whisdom-based stringed musical instruments. The results of this study are expected to provide excellent benefits in research and development of science for lecturers, students and the wider community. The method used in this study is a qualitative approach and exploration besides art. The process of finding data and information is carried out thoroughly for overall and complete information about the diversity of traditional stringed musical instruments in North Sumatra. Data collected from two sources, namely primary data and secondary data. Primary data is obtained from the techniques of in-depth interviews (in-depth interviews) and joint observation (participant observation) which aims to explore data focused on focus groups (focus group discussions). The selection of informants is carried out on grouping key informants consisting of makers, users, experts and academics of traditional music. Secondary or primary data then organized for later exploration in creating musical instruments concocted with the diversity of local whisdom in North Sumatra. The results of this study are: Taking into account the various forms of musical instruments and the areas of the tones of each related instrument, then formulated to emit the tone by adopting and exploring existing instruments.